Monetary Policy and Asset Prices in a Small Open Economy: A Factor-Augmented VAR Analysis for Singapore - CHOW, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2009)
The ongoing global financial turmoil has revived the question of whether central bankers ought to tighten monetary policy preemptively in order to head off asset price misalignments before a sudden crash triggers financial instability. This study explores the issue of the appropriate monetary policy response to asset price swings in the small open economy of Singapore. Empirical analysis of monetary policy based on standard VAR models, unfortunately, is often hindered by the use of sparse information sets. To better reflect the extensive information monitored by Singapore’s central bank, including global economic indicators, we augment a monetary VAR model with common factors extracted from a large panel dataset spanning 122 economic time series and the period 1980q1 to 2008q2. The resulting FAVAR model is used to assess the impact of monetary policy shocks on residential property and stock prices. Impulse response functions and variance decompositions suggest that monetary policy can potentially be used to lean against asset price booms in Singapore.